Does Gestational Diabetes History Increase Epicardial Fat and Carotid Intima Media Thickness?. Issue 10 (26th March 2014) - Caliskan, Mustafa; Caklili, Ozge Telci; Caliskan, Zuhal; Duran, Cevdet; Çiftçi, Faika C.; Avci, Enver; Güllü, Hakan; Kulaksizoglu, Mustafa; Koca, Harun; Muderrisoglu, Haldun
<x xml:space="preserve">Abstract</x> Background Gestational diabetes mellitus (GDM) is defined as glucose intolerance that has begun during pregnancy. Recent studies have proven that development of atherosclerosis may be established in this population even without presence of type 2 diabetes. For assessment of atherosclerosis, epicardial fat thickness (EFT) is recently being used as a surrogate marker. In this study, we aimed to prove that women with GDM history are more inclined to have higher EFT levels than women without GDM history. Methods Sixty‐two patients with previous GDM and 33 age‐ and sex‐matched controls were allocated. Epicardial fat thicknesses of the subjects were measured with transthorasic echocardiography and carotid intima media thickness (c‐IMT) was measured with ultrasound. Insulin resistance (IR) of each subject was assessed with Homeostasis model of assessment—insulin resistance (HOMA‐IR). Results Carotid IMT and EFT were significantly higher in previous GDM group than controls. Serum gamma‐glutamyl transferase (GGT), uric acid, and high‐sensitivity C‐reactive protein (hs‐CRP) levels were also found significantly higher in the patients with previous GDM as compared to the controls. We observed that carotid IMT (β = 310, P = 0.003), total cholesterol (β = 315, P = 0.002), BMI (β = 308, P = 0.002), HbA1c (β = 227, P = 0.018), and HOMA‐IR (β = 184, P = 0.049) were independently correlated with EFT. Conclusions Although the number of patients included in this study is limited, high EFT results may indicate presence of atherosclerosis in women with previous GDM.